Re-canonizing the Shanhaijing in the world (literature): the myth, the play and the comic book. Issue 2 (3rd May 2020) - Gallo, Simona
ABSTRACT: In 1989, Gao Xingjian 高行健 – a Chinese-born artist (1940), French citizen (1997) and Nobel Prize for Literature (2000) – gave birth to the Shanhaijing zhuan 山海經傳 ( Of Mountains and Seas ), a tragicomedy in three acts. As the title evokes, the lyrical drama is inspired to the ancient mythology of the Shanhaijing 山海經 ( The Classic of Mountains and Seas ), an encyclopaedic cosmography compiled from the Warring States period to the Western Han dynasty (4 th -1 st century BC). By creating this play, the Nobel Laureate re-codified a Chinese canonical work into a contemporary play. After that, an American comic book based on Gao tragicomedy appeared, Guideways through Mountains and Seas . Based on the assumption that the three works are genealogically related, the paper describes the changes taking place through the process of transposition, by focusing on the macro- and micro-textual profiles. Thus, it re-discusses the canon and the dynamics canonicity, by revealing how translation and intertextuality both ensue from the canonization of literature (and world literature) and empower its circulation and consecration beyond frontiers.